Telaah Ketepatan dan Keakuratan dalam Penentuan Arah Kiblat - Miswanto Miswanto (Institut Agama Islam Negeri (IAIN) Tulungagung, 2015)
In determining the position of kiblat, commonly there are two techniques: calculation and measurement. One of the calculation techniques is the use of spherical trigonometry formula. Spherical trigonometry utilizes the formula of spherical triangle with earth as model. Another formula useful for determining of kiblat is the formula of analogy by Napier. The function of the formula is to calculate one angle between two places in the spherical triangle. This research is comparing the implementation of spherical trigonometry and Napier’s analogy. The finding reveals that spherical trigonometry is more accurate in determining the position of kiblat than Napier’s analogy.